COMPLETE AUDIT CYCLE: PERI-OPERATIVE GLYCEMIC CONTROL IN CMH LAHORE - BUTT, SZ; HAFEEZ, T; SIDDIQUI, MMA; FAYYAZ, T; AZIZ, I; IMRAN, A; AHMED, Y; ARIF, B (Biological and Clinical Sciences Research Journal, 2023)
Hyperglycemia is associated with an increased risk of complications in patients undergoing surgery. Hyperglycemia from diabetes must be differentiated from stress-induced hyperglycemia, which typically presents post-operatively and resolves as the surgery-induced stress subsides. It is imperative to differentiate between the two due to the severe complications of diabetic hyperglycemia, which can often be confused with its stressed induced counterpart. Good glycemic control is the best strategy to avoid post-operative complications and morbidity. An assessment of peri-operative blood glucose levels of known diabetics admitted to CMH Lahore was done, and recommendations were introduced to achieve better glycemic control. Subsequently preventing post-surgical complications, improving wound healing and overall recovery, and ultimately decreasing morbidity. The aim of the audit was the assessment of peri-operative glycemic control in known diabetics admitted for surgery in CMH Lahore. Existing problems regarding poor glycemic control were identified, and recommendations were given to rectify said problems. We aimed to study the effectiveness of glucose control due to these planned interventions. Patients were included based on eligibility criteria, and a record of the patients was updated daily on the Excel sheet using the glucose control audit tool (attached below). The highest BSR reading per day was added. Good or poor glycemic control was determined by the highest BSR readings on post-op days 0, 1, and 2. If 2 or more readings met the criteria for good glycemic control, the patient was labeled to have good glycemic control. In Cycle 1, patients were managed peri-operatively with insulin as per the sliding scale. 13% of patients had good glycemic control on this regimen. Interventions were introduced for Cycle 2, with the recommendation of altering insulin/drug regimens as per NHS/ADA guidelines. 16.6% of patients were found to achieve good glycemic control; however, it was noted that these recommendations were not followed consistently. Based on the results, it can be concluded that the management of inpatient diabetes is a team effort, interventions recommended using established guidelines should be followed stringently, and existing protocols should be updated accordingly. Proper management of inpatient hyperglycemia starts with each team member performing their respective role to their best; this is vital in preventing post-operative complications associated with poor glycemic control.